HISTORIOGRAFI TRADISIONAL, RAJA-RAJA MELAYU, DAN KEKUASAAN DALAM HIKAYAT NEGERI JOHOR - Mu'jizah, Mu?jizah (ATAVISME, 2018)
The aim of the research is to find the elements of history  from the kings of Malay in Riau, time of the power, and historic event in Hikayat Negeri Johor. The qualitative method was used with descriptive analysis and comparation study. Results of the study proved that Hikayat Negeri Johor contains many historical elements consisting of figure of the Malay kings, background place and time, and historical events related to their politics and their power. The politics pertain to the dominion of the kings related to some periods, from Sultan Abdul Jalil Syah until Sultan Mahmud. The historical elements can proved from comparation of many sources. The conclusion is that this work has highly historical value. This work can be considered to be used in compiling a local history. The content of the historical elements in this work includes six characters of Malay Kings in Riau, places and times of event, and historical events. Based on the comparation study, it was found that many historical events in Hikayat Negeri Johor are proven facts in history.